2001
DOI: 10.1159/000048758
|View full text |Cite
|
Sign up to set email alerts
|

Expression of <i>TCL1</i> in Hematologic Disorders

Abstract: Objective:TCL1, MTCP1 and TCL1b are three members of a new family of oncogenes that are expressed in T cell leukemias of ataxia telangiectasia patients (T-PLL, T-CLL). TCL1 is located at 14q32.1 and activated by juxtaposition to the α/δ-locus at 14q11 or β-locus at 7q35 of the T cell receptor during the reciprocal translocations t(14;14)(q11;q32), t(7;14)(q35;q32), or inversion inv(14)(q11;q32). TCL1 encodes a predominantly cytoplasmic protein of 114 aa (14 kD) of unknown function. Recent studies suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…28,30,41 In nonneoplastic lymphoid cells, TCL1 is expressed in a small subset of thymocytes, in plasmacytoid dendritic cells, and in B cells up to the germinal center (GC) stage of maturation. 5,31,35,[42][43][44][45][46][47] In nonneoplastic T cells, TCL1 is expressed only at the earliest stages of thymocyte development before the TCR signaling pathway is assembled. 4,42 Similarly, in nonneoplastic B cells, TCL1 expression is lost at the GC stage of maturation when B-cell receptor (BCR) signaling through appropriately presented antigen occurs.…”
Section: Discussionmentioning
confidence: 99%
“…28,30,41 In nonneoplastic lymphoid cells, TCL1 is expressed in a small subset of thymocytes, in plasmacytoid dendritic cells, and in B cells up to the germinal center (GC) stage of maturation. 5,31,35,[42][43][44][45][46][47] In nonneoplastic T cells, TCL1 is expressed only at the earliest stages of thymocyte development before the TCR signaling pathway is assembled. 4,42 Similarly, in nonneoplastic B cells, TCL1 expression is lost at the GC stage of maturation when B-cell receptor (BCR) signaling through appropriately presented antigen occurs.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] Reports of TCL1 protein expression in CLL have been limited to a few small immunohistochemical studies without immunophenotypic, genotypic, or molecular correlations and did not comment on intratumoral regulation of TCL1 levels. 13,14,16 Here, we show that CLL also largely maintains the normal Bcell developmental pattern of TCL1 regulation with lower levels in the post-GC/mutated tumor subset. Indeed, we found that 10-14% of CLL are TCL1 negative and an additional proportion (27% by IHC) shows low protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…3,[10][11][12] TCL1 has also been shown to be highly expressed in most Bcell tumors, however, chromosome aberrations that constitutively activate TCL1 are not found and thus its role as a B-cell oncogene is unclear. [13][14][15][16][17][18] However, when driven by IgH Em enhancer elements, human TCL1 overexpression in mice produces B-cell tumors preceded in some cases by preneoplastic CD5 þ /IgM þ B-cell expansions that resemble early chronic lymphocytic leukemia (CLL). 15,19,20 To clarify TCL1's role in human CLL, we present here the first complete assessment of the regulation of TCL1 in the different molecular and immunophenotypic subsets of CLL.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 TCL-1 protein function has been studied predominately in T-cells, in which it has been demonstrated to bind to the pleckstrin homology domain of Akt and to enhance both AKT enzymatic activity and translocation from cytoplasm to nucleus. [6][7][8] Introduction of tcl-1 under the control of a T-cell-specific lck gene promoter in transgenic mice results in a mature T-cell leukemia late in life that is similar to human T-cell PLL.…”
Section: Introductionmentioning
confidence: 99%